Poverty and Non-Natural Deaths among Former Mineworkers and in their Families in Transkei Region of South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Thousands of former mineworkers across former Transkei have already passed on, are disabled, or died due to either mining related diseases or non-natural ways of dying such as accidents, suicide, or homicide. Many ex-mineworkers have died prematurely, placing a strain on their families. This has led to dysfunctional families and has created the conditions for children from these families to commit crime. Compensation could be claimed for mining related maladies, but the non-natural deaths are unbearable for a resource-stricken family. Objective: To highlight the problem of poverty and non-natural deaths among former mineworkers, and to relate the impact on their families. Method and Material: This research, a retrospective qualitative study on former mineworkers and their children, was carried out in 2000-01 at the forensic pathology laboratory of Umtata General Hospital complex, Mthatha, Eastern Cape, South Africa. The records of interviews performed during medicolegal autopsies in 2000 and 2001were reviewed at Umtata (Mthatha) General Hospital mortuary. The interviews were routinely performed in relation to victims who were admitted at the Umtata (Mthatha) General Hospital mortuary.Results: Eighty-four family records were analysed. Of these, 21 (25%) were found to be former mineworkers and their immediate family members. There were five mineworkers and 15 children of mineworkers. Only one was the spouse of a mineworker who had died unnaturally, and one person was unaccounted for in these numbers. Three mineworkers died because of firearm injuries, one was assaulted by someone with a knobkerrie, and another one died because of alcoholic intoxication. Two of them had heavy drinking habits. Three mineworkers were unemployed. The causes of unnatural deaths were as follows: five stabbed, two from firearm injuries, one from a motor vehicle accident, one assaulted with blunt object, and three committed suicides by hanging and poisoning. Most of the victims consumed alcohol. Conclusion: A high number of former mineworkers died an unnatural death. Poverty could be an associated as an underlying cause of death.